LOL - Shamberg, Michael; Sher, Stacey; Cyrus, Tish, 1959-; Azuelos, Lisa; Ainouz, Kamir; Moore, Demi; Cyrus, Miley, 1992-; Greene, Ashley, 1987-; Sevani, Adam G., 1992- (Lionsgate, 2012)
Miley Cyrus stars as a teen girl navigating through the peer pressures of high school romance and friendship, while dodging her protective mother.